Effect of Incorporation of Jackfruit (Artocarpus heterophyllus) Seed Flour on the Quality of Cookies - Maskey, Bunty; Subedi, Sarmila; Shrestha, Nabindra Kumar (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to determine the effect of jackfruit seed flour incorporation on the quality of cookies. D-optimal mixture design has been employed for formulating the recipe of cookies. Five different formulations of cookies containing 0, 12.5, 25, 37.5, and 50 parts jackfruit seed flour were prepared. The prepared cookies are subjected to sensory evaluation by ten semitrained panelists for consumer acceptability. The obtained data have been statistically analyzed using two-way ANOVA (no blocking) at 5% level of significance. From the mean sensory scores, 12.5 parts jackfruit seed flour incorporation was selected as the best formulation and subjected to proximate analysis. The protein, fat, fiber and ash contents are significantly (p<0.05) higher in jackfruit seed flour incorporated cookies than wheat flour cookies (control). The phytate and oxalate contents were also found to be significantly (p<0.05) higher in jackfruit seed flour incorporated cookies than control but were below tolerance level and safe for consumption.